Pengaruh Pelatihan Kewirausahaan, Religiusitas, Kreativitas Terhadap Minat Berwirausaha Dengan Motivasi Sebagai Variabel Intervening - Laksono, Wahid Bayu; Soleh, Mohammad (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2022)
The purpose of this study was to determine the effect of entrepreneurship training, religiosity, and creativity on interest in entrepreneurship by using motivation as an intervening variable. The main finding in this study is about how far the motivational variable can mediate between the independent variables and the dependent variable. The type used in this study is quantitative using a sample of 87 respondents. The results of the study found that: (a) motivation was not able to mediate the effect of training entrepreneurship on entrepreneurial interest From the results of research calculations with a t-count value of 1.61807136606 <1.66298 with a significance level of 0.05, (b) motivation is not able to mediate the influence of religiosity on entrepreneurial interest. From the results of research calculations with a t-value of 1.35580366084 < 1.66298 with a significance level of 0.05, and ( c) motivation is able to mediate the effect of creativity on interest in entrepreneurship. From the results of research calculations with a t value of 2.33241078441 > 1.66298 with a significance level of 0.05. Thus, motivation can only mediate creativity to interest in entrepreneurship.